Integration of the Supply Chain Management and Development of the Marketing System - Iryna Perevozova; Liliana Horal; Andriy Mokhnenko; Nataliia Hrechanyk; Andriy Ustenko; Oksana Malynka; Lilya Mykhailyshyn (International Journal of Supply Chain Management, 2020)
Abstract— This paper aims to develop a deeper understanding of integration between supply chain management and marketing by marketing system in conditions of competition among regions. The place of marketing in the economic system of the region is determined; the emphasis is placed on the study of the region as a product, the evolution of marketing, the identification of the essence of marketing in the system of regional policy. Author's approach to the regions as a kind of competing corporations for resources and consumers is developed. To achieve the goal of the study authors implied theoretical method to provide scientific literary sources analysis, general-scientific method, for instance analysis, synthesis, comparison of received information. On the basis of analysis and systematization of data on the development of the region and existing marketing strategies, a marketing strategy for the region, which consists of eight stages, is designed to increase the region's popularity, that is, to create its positive image and improve the competitiveness of enterprises located in the region. This study provides information that is of particular interest for marketing researchers and practitioners.  The set of marketing methods is offered, with the help of which it is possible to assess the rationality of the region's development and provide information for further prediction of socio-economic development of the region. The marketing methods are understood as the set of methods and ways of thinking, allowing on the basis of the analysis of retrospective data, exogenous (external) and endogenous (internal) links of the object, as well as their measurements within the framework of the phenomenon or process under consideration, to derive certain authenticity judgments regarding its future development.